The new root dictionary by Oleksa Riznykiv (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article examines the new root dictionary by O. Riznykiv “Ukrainian word families. The second edition: The word families of the Spirit” (2015) which has not been the object of special consideration yet. It substantiates the value of the dictionary in the study of the Ukrainian language and clarifies the author’s innovation in the study of the language issues. The dictionary by O. Riznykiv differs from existing morpheme and words building dictionaries, because its main unit is not just words, but the part of the word without the prefix, that combines the root, the suffixes and the ending of the word. O. Riznykiv introduces a Ukrainian term for it “vidkorinok” that stands for a word family derived from the same root. The examples of the word family are given in six columns and in an alphabetical order (verbs, nouns, masculine nouns, neuter nouns, feminine nouns, unchanging and plural forms, adjectives and gerund forms of the masculine gender). The author of the dictionary refers to that group also the words concerning individual names (nicknames, the names of settlements and the names of Ukrainian water areas).Riznykiv counted the number of each word family and its components that show the arrangements of this root, its derivation possibilities and its depth and versatility features. The author introduces a special Ukrainian term for such characteristic description of the word family. He calls it “chilnik”. In addition he illustrates every word family with examples of Ukrainian proverbs and sayings, from Ukrainian writers and his own poetry.In the root dictionary counts 54 word families, but at the time of its publishing the number of them approached 2080 units. The author submits them separately on a disk and he continues to add new ones. Now there are 2288 word families and its number is growing daily. The dictionary by O. Riznykiv also contains popular and scientific articles on the Ukrainian language mysteries and speech paradoxes. The author compares different words, shows their arrangements, finds out which of the words prevails and makes some conclusions. Stressed: the new root dictionary by O. Riznykiv is original and distinctive. It proves the hard work of the researcher, shows his great love to the Ukrainian language. The dictionary opens new horizons for scientists in the study of the history of the Ukrainian language, its proto-Slavic origin, the process of word building, variety of suffixes and for every Ukrainian citizen that should be proud of the richness of his language and its ancient origin. O. Riznykiv tried to “compute” the Ukrainian language, make the “inventory” of Spirit with the help of word families that have formed for thousands of years in the minds of the Ukrainians.
Keywords: morpheme and word building dictionaries; the new root dictionary; the word family; Ukrainian language terms; “vidkorinok”; “chilnik”